1986
DOI: 10.1111/j.1471-0528.1986.tb07813.x
|View full text |Cite
|
Sign up to set email alerts
|

Human amnion in the treatment of vaginal malformations

Abstract: Vaginoplasty using human amnion has been performed in 27 patients aged from 13 to 28 years. Excellent epithelialization occurred with good functional results; the technique appears to be preferable t o other surgical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 9 publications
0
26
0
3
Order By: Relevance
“…The HAM can produce a wide array of growth factors and provide a healthy new substrate suitable for re-epithelization and epithelial healing (Wilshaw et al 2006). Amnion allografts are widely applied in ophthalmology, plastic surgery, dermatology, and gynecology Santos et al 2005;Rinastiti et al 2006;Meller et al 2000;Morton and Dewhurst 1986). The low cost of amnion graft preparation and the very good clinical results in multipurpose applications have made it a valuable material for tissue banking and a viable alternative to other natural (i.e., preserved human skin) and synthetic wound dressings.…”
Section: Discussionmentioning
confidence: 99%
“…The HAM can produce a wide array of growth factors and provide a healthy new substrate suitable for re-epithelization and epithelial healing (Wilshaw et al 2006). Amnion allografts are widely applied in ophthalmology, plastic surgery, dermatology, and gynecology Santos et al 2005;Rinastiti et al 2006;Meller et al 2000;Morton and Dewhurst 1986). The low cost of amnion graft preparation and the very good clinical results in multipurpose applications have made it a valuable material for tissue banking and a viable alternative to other natural (i.e., preserved human skin) and synthetic wound dressings.…”
Section: Discussionmentioning
confidence: 99%
“…Use of an amnion graft to cover the newly created vaginal space has been associated with very good outcome (preservation of a functional vaginal space) ranging from 88 to 100% [127,[135][136][137][138][139][140]. However, in the past years, concerns have been raised regarding the potential transmission of infectious agents such as hepatitis and HIV, and therefore, the method has been abandoned [141].…”
Section: The Mcindoe Operationmentioning
confidence: 99%
“…On the other hand, HAM has abundant natural cartilage components, which are important in the regulation and maintenance of normal chondrocyte metabolism (Jin et al, 2007); this suggests that the HAM is an excellent candidate for use as native scaffold for cartilage tissue engineering (Niknejad et al, 2008). Amnion allografts are widely applied in ophthalmology, plastic surgery, dermatology, and gynecology (Tejwani et al, 2007;Santos et al, 2005;Rinastiti et al, 2006;Meller et al, 2000;Morton & Dewhurst, 1986). A recent study demonstrated the potential use of the HAM as a scaffold to support human chondrocyte proliferation in cell therapy to repair human OA cartilage (Díaz-Prado et al, 2010c).…”
Section: Scaffoldsmentioning
confidence: 99%